Long-term dietary shifts in a generalist predator, the wolverine (Gulo gulo) - Massé, Clément F.; Hiltunen, Tamara A.; Lansink, Gerhardus M. J.; Holmala, Katja; Isomursu, Marja; Kojola, Ilpo; Aspi, Jouni; Welker, Jeffery M. (Frontiers in Ecology and Evolution, 2023)
Over the last hundred years, many large carnivore species have suffered range contractions, population losses, and habitat alterations that may be influencing their dietary preferences. To identify shifting isotopic niches and reconstruct past and present diets from species of high conservation concern, stable isotope analysis (SIA) of  13 C and  15 N values of tissue from museum collections and ongoing non-invasive monitoring programs offers an effective approach.Here, we assessed the long-term alterations in the trophic structure of a generalist large carnivore over a time of population loss and recovery. Wolverine stable carbon (δ 13 C) and nitrogen (δ 15 N) isotopes were measured in hair samples collected from 44 individuals in Finland for the period 1905-2020, and potential dietary were quantified using isotopic niche metrics shifts in two study areas. We provide evidence of a long-term diet shift in Finnish wolverines, with a temporal depletion of hair's δ 13 C (β = -0.016‰, R²= 0.46, p <0.001). Correspondingly, there was a shift in the isotopic niches of the Historical population (before the year 2000) and Recent population (after 2000), with the niche overlap between the Historical and Recent periods being only 33% throughout Finland, and even lower in the two study areas (22% to 24%). The breadth of the isotopic niche, however, did not significantly differ between the two periods, suggesting that despite a change in diet composition, wolverines did not specialize more. The trophic level of wolverines in Finland was stable throughout the study period, with no significant change in δ 15 N with time (β = 0.0055‰, R² = 0.043, p = 0.17). In summary: A) the strong trophic resilience of this top predator was shown by the stability of its niche breadth and trophic level feeding regime during periods of population decline and recovery as well as during a period of major anthropogenic alterations in their environment; B) the use of SIA methods on historical and recent hairs provided a unique tool to unravel long-term changes in wolverine feeding strategies.